Оптимізація діагностики та лікування хворих на міопію середнього і високого ступеня при факоемульсифікації катаракти - Красножан, О. В.; Луценко, Ніна Степанівна; Жабоєдов, Д. Г.; Обухова, М. С.; Krasnozhan, O. V.; Lutsenko, N. S.; Zhaboiedov, D. G.; Obukhova, M. S. (My University, 2021)
Мета. Оптимізувати діагностику та лікування хворих на міопію середнього і високого ступеня при факоемульсифікації катаракти. Phacoemulsification with implantation of intraocular lens (IOL) is a leading technology in cataract surgery, but it is accompanied by an increased (1,5 – 2,5 times) risk of intraoperative and postoperative complications in patients with degenerative myopia: progression of dystrophic processes in the central and peripheral parts. In the case of phacoemulsification, it is necessary to take measures aimed identifying risk factors in patients with degenerative myopia in the preoperative period and to choose minimally invasive approaches at each stage of the surgery.
Optimization of diagnosis and treatment of patients with moderate severe and high degree myopia during phacoemulsification cataract surgery